Mediaeval Researches from Eastern Asiatic Sources : Fragments Towards the Knowledge of the Geography and History of Central and Western Asia from the 13th to the 17th Century: Volume I.: Fragments Towards the Knowledge of the Geography and History of Central and Western Asia from the 13th to the 17th Century: Volume I. ([2013?]) - Bretschneider, E, 1833-1901
No abstract available